1990
DOI: 10.1111/j.1651-2227.1990.tb11377.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Rooming‐in/not Rooming‐in and Breast‐Feeding Variables

Abstract: We studied the relationship between rooming-in/not rooming-in and breast-feeding variables such as breast feeding frequency, breast milk intake, supplements of other human milk or 5% glucose solution, cumulative weight loss, weight recovery and hyperbilirubinemia. We found that the breast feeding frequency was significantly higher in infants rooming-in than in those not rooming-in. Intake of breast milk on days 3 and 5 was significantly lower and maximum weight loss was significantly higher in infants rooming-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 19 publications
1
36
0
2
Order By: Relevance
“…During each opportunity to breastfeed, maternal and newborn beta-endorphin levels rise, "rewarding and reinforcing maternal and infant interactions" (Buckley, 2014). For decades, researchers have reported that mothers who room-in with their babies score higher on tests that measure mothering confidence, and babies who room-in with their mothers have more quiet sleep than those who are separated from their mothers (Keefe, 1987(Keefe, , 1988Yamauchi & Yamanouchi, 1990).…”
Section: Keeping Mothers and Babies Together Beyond The Moment Of Birthmentioning
confidence: 99%
“…During each opportunity to breastfeed, maternal and newborn beta-endorphin levels rise, "rewarding and reinforcing maternal and infant interactions" (Buckley, 2014). For decades, researchers have reported that mothers who room-in with their babies score higher on tests that measure mothering confidence, and babies who room-in with their mothers have more quiet sleep than those who are separated from their mothers (Keefe, 1987(Keefe, , 1988Yamauchi & Yamanouchi, 1990).…”
Section: Keeping Mothers and Babies Together Beyond The Moment Of Birthmentioning
confidence: 99%
“…The benefits of rooming-in in hospital were demonstrated in the late 1980s and early 1990s in a number of key studies [59,60,[81][82][83] which showed that rooming-in facilitates mother-infant contact, enabling mothers to perform all aspects of their infant's care [84], and that mother-infant separation at night does not result in an increase in either the quantity or quality of maternal sleep or in maternal alertness the following day [59,83]. They also showed that removing infants to nurseries resulted in significantly less infant sleep and more crying than for infants remaining in their mothers' rooms [60]; less frequent breastfeeding [81]; and greater likelihood of breastfeeding failure [82]. Twenty-four-hour rooming-in is now standard practice in progressive and WHO/UNICEF Baby-Friendly accredited hospitals worldwide.…”
Section: Maternal and Infant Sleep On The Postnatal Wardmentioning
confidence: 99%
“…Большая потеря массы тела в первые дни жизни, прово-цирующая гипербилирубинемию, связана с нарушением принципов ГВ, рекомендованных ВОЗ, и может быть снижена путем образования медицинских работников и матерей [31]. В частности, частота прикладывания к груди минимум 11 раз в день, начиная с первого дня жизни, снижает уровень билирубина сыворотки крови ребенка к 3-6-му дню жизни [32,33]. Кроме того, задержка в инициировании грудного вскармливания после первого часа жизни и допаивание водой либо до начала грудного вскармливания, либо в добавление к грудному вскармливанию значительно снижает частоту ГВ и вызывает повышение концентрации билирубина в сыворотке крови младенца [34].…”
Section: Arias Et Al (1963) [11] и Newman Et Al (1963)unclassified